(untitled) - Atkins, Peter (New York, 2014)
With its modern emphasis on the molecular view of physical chemistry, its wealth of contemporary applications, vivid full-color presentation, and dynamic new media tools, the thoroughly revised new edition is again the most modern, most effective full-length textbook available for the physical chemistry classroom.
Keywords: Chemistry, Physical and theoretical,Lý thuyết hóa lý